The Impact of Internal and External Factors on Commercial Bank Performance in the United States - Ezepue, Nkolika (2020)
The global financial crisis of 2008 caused widespread contagion of the global financial system and the United States financial system. Having a deep knowledge of the determinants of bank performance is important for achieving a strong, sustained, and healthy financial system. Therefore, this study investigates the impact of internal and external factors on commercial bank performance in the United States. To deepen the analysis, the US commercial banks are categorised by size and capital adequacy. A fixed-effects regression technique was used on panel data of US commercial banks obtained from Orbis Bank Focus database, World Bank, and US Bureau of Labour Statistics, ranging from 2011-2020. The findings show that both internal and external factors contribute to the performance of commercial banks. The results emphasised the need to treat banks heterogeneously. When banks were categorised by size, apparent differences in the impact of capital and liquidity on bank profitability was seen. Inflation and growth had varying impacts depending on whether banks have low or high capital levels. This study contributes to knowledge regarding bank performance. Uniquely, this is the first study to categorise banks via capital adequacy, thus enriching existing literature on bank performance.